PENGARUH MOTIVASI, KEMAMPUAN KERJA DAN PENGAWASAN TERHADAP KINERJA PEGAWAI KANTOR KECAMATAN PENAJAM KABUPATEN PENAJAM PASER UTARA - Firman Usman (Jurnal Paradigma (JP), 2017)
This Research aims to explore the influence of motivation, work skill and supervision on employee’s work performance. This research uses research methods, namely: (1) the rating scale Method, (2) methods of checklist, (3) directional choices Method (4) critical incident Method, (5) the method of rating scale (6) evaluation methods of the field, (7) Test Methods and observations (8) method of komperatif approach. The first Hypothesis test shows that there are strong relations between motivations, work skill and supervision on employee’s work performance. While the Second Hypothesis test indicate that the dominant factor motivation factors.